2017
DOI: 10.14814/phy2.13328
|View full text |Cite
|
Sign up to set email alerts
|

Highly suggestive preliminary evidence that the renal interstitium contracts in vivo

Abstract: To learn more about controlling renal interstitial hydrostatic pressure (RIHP), we assessed its response to renal medullary direct interstitial volume expansion (rmDIVE = 100 μL bolus infusion/30 sec). Three experimental series (S) were performed in hydropenic, anesthetized, right‐nephrectomized, acute left renal‐denervated and renal perfusion pressure‐controlled rats randomly assigned to groups in each S. S1: Rats without hormonal clamp were contrasted before and after rmDIVE induced via 0.9% saline solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Given the sui-generis architecture of the renal interstitium [1] and supported both in the well-known phenomenon of cellular subcutaneous tissue contraction [2] and in the fact that renal medullary interstitial cells in culture contract in response to endothelin and arginine vasopressin [3], we recently provided [4] highly suggestive preliminary evidence that the renal interstitium contracts reactively in vivo . We reported that, in hydropenic rats subjected to left renal denervation, hormonal clamping, and renal arterial pressure control, the renal medullary Direct Interstitial Volume Expansion ( rmDIVE ) induced by a 0.9% saline bolus infusion (100 μL / 30 s) into the left renal medullary interstitium brought about a biphasic renal interstitial hydrostatic pressure (RIHP) response (early: ~1 mmHg and late: ~ 4 mmHg).…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Given the sui-generis architecture of the renal interstitium [1] and supported both in the well-known phenomenon of cellular subcutaneous tissue contraction [2] and in the fact that renal medullary interstitial cells in culture contract in response to endothelin and arginine vasopressin [3], we recently provided [4] highly suggestive preliminary evidence that the renal interstitium contracts reactively in vivo . We reported that, in hydropenic rats subjected to left renal denervation, hormonal clamping, and renal arterial pressure control, the renal medullary Direct Interstitial Volume Expansion ( rmDIVE ) induced by a 0.9% saline bolus infusion (100 μL / 30 s) into the left renal medullary interstitium brought about a biphasic renal interstitial hydrostatic pressure (RIHP) response (early: ~1 mmHg and late: ~ 4 mmHg).…”
Section: Introductionmentioning
confidence: 57%
“…The next step in the present study was to determine the ideal volume of the micro-bolus to be injected and the effective dose of α-TNS for a single local renal injection. To avoid inducing significant rmDIVE via a 100 μl bolus infusion of SS, which by itself increases RIHP [4], preliminary experiments suggested the use of a sudden 3–5 μl micro-bolus injection. We exploited the countercurrent drug-trapping mechanism present in the renal medullary interstitium, which enables drugs to be retained longer with very small quantities escaping into systemic circulation [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations